Abjection of the Other in Richard Matheson’s I Am Legend: The Subject’s Deterrence Strategy for Becoming the Abject - Mohseni, Hossein (Text Matters: A Journal of Literature, Theory and Culture, 2023)
Richard Matheson’s I Am Legend (1954) is about the volatile relationship between Robert Neville—the sole survivor of the human race—and vampires as the members of a brave new world order. While many critics tend to read the relationship between Robert and the vampires as the colonizer and the colonized, this article sees the need to devise a paradigm to acknowledge the critical merits of all these postcolonial and racial readings without overemphasizing the validity of any of the mentioned readings at the expense of the other. The paradigm shows the journey of a subject who initially thought that he is in absolute control, but later is made to realize that, in his insistence on this position, he is actually being swayed towards marginalization and abjection. At the same time, the initially abject and marginalized vampires assume the position of dominance and normalcy at the end of the novel. In order to reach this understanding, the study draws on Julia Kristeva’s theoretical conceptualization of abjection.